The livelihood effects of industrialization on displaced households: Evidence from Falta Special Economic Zone - Saumik Paul; Vengadeshvaran Sarma (The University of Nottingham, Centre for Research in Economic Development and International Trade (CREDIT), 2013)
Much of the debate on industrialization and displacement has, so far, focused on the optimum compensation for affected households. Our recently concluded study, comprising of a sample of 1017 households including 630 affected (displaced and land acquired) and 387 unaffected households, looks at the long-term livelihood effects of the Falta Special Economic Zone (FSEZ) in West Bengal, India. The main findings indicate a lower labour market participation rate among affected household members. However, members of displaced households show the highest work participation rate in the industrial zone but with a lower return to education than others. Women earn about 17 percentage points less compared to men after controlling for education and experience and this gap is 5 to 10 percentage points higher for FSEZ employees; but this gap is narrowing over time likewise the gender education gap.
Keywords: O14; J16; J21; J31; 330; Industrialization; Special Economic Zones; Rural livelihoods; West Bengal; India